2004
DOI: 10.1172/jci19657
|View full text |Cite
|
Sign up to set email alerts
|

Critical roles of c-Jun signaling in regulation of NFAT family and RANKL-regulated osteoclast differentiation

Abstract: IntroductionThe amount of bone remodeling is controlled by the balance between bone formation and bone resorption (1-3). Many osteopenic diseases, including osteoporosis, rheumatoid arthritis, Paget disease, and lytic bone metastases of malignancies are characterized by progressive and excessive bone resorption by osteoclasts, which are multinucleated giant cells that originate from hematopoietic cells (2). A TNF family member, receptor activator of NF-κB ligand (RANKL), which is expressed as a membrane-bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
260
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 258 publications
(285 citation statements)
references
References 43 publications
20
260
0
5
Order By: Relevance
“…JNK1 activated by RANKL protects osteoclast precursors from RANKL-induced apoptosis and regulates osteoclastogenesis through the phosphorylation of c-Jun, a component of the dimeric transcription factor AP-1 [25]. C-Fos, another component of AP-1, is an essential transcription factor for osteoclast differentiation [21,22,26]. Up-regulation of c-Fos by the p38 pathway has been recently reported [27].…”
Section: Discussionmentioning
confidence: 99%
“…JNK1 activated by RANKL protects osteoclast precursors from RANKL-induced apoptosis and regulates osteoclastogenesis through the phosphorylation of c-Jun, a component of the dimeric transcription factor AP-1 [25]. C-Fos, another component of AP-1, is an essential transcription factor for osteoclast differentiation [21,22,26]. Up-regulation of c-Fos by the p38 pathway has been recently reported [27].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that the expression of dominant-negative forms of p38 MAPK and MKK6 in RAW264.7 cells inhibited RANKL-induced differentiation of RAW264.7 cells into osteoclasts (Matsumoto et al 2000). Moreover, addition of luteolin to osteoclast cultures strongly inhibited the expression of NFATc1, which is a key transcription factor for the expressions of TRAP and other osteoclastogenesis-associated genes (Ikeda et al 2004;Matsumoto et al 2004;Sharma et al 2007). Therefore, the effects of luteolin on osteoclastogenesis are probably mediated by ATF2, downstream of p38 MAPK pathway.…”
Section: Discussionmentioning
confidence: 99%
“…8 It was suggested that JNK participates to Oc differentiation by playing a role in RANKL induction of NFATc1 expression through c-Jun activation. 9 Specific activation of JNK1, but not JNK2, by RANKL in bone marrow monocytes (Oc precursors) and selective requirement of JNK1, but not JNK2, activity for efficient OC differentiation were reported. 10 The involvement of p38 in osteoclastogenesis has been demonstrated by the treatment of bone marrow precursor cells with pharmacological inhibitors of the kinase.…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of MKK7 in Oc differentiation from the precursors in spleen cells and from RAW264.7 cells was demonstrated by using a siRNA and DN form, respectively. 9,14 The expression of a DN form of MKK6 was shown to inhibit Oc differentiation form RAW264.7 cells. 13 Knowledge on the upstream kinases (MAPKKKs) that activate MKKs for Oc differentiation has remained limited.…”
Section: Introductionmentioning
confidence: 99%